Effects of a decade of organic fertilizer substitution on vegetable yield and soil phosphorus pools, phosphatase activities, and the microbial community in a greenhouse vegetable production system - Yin-jie ZHANG; Wei GAO; Hao-an LUAN; Ji-wei TANG; Ruo-nan LI; Ming-yue LI; Huai-zhi ZHANG; Shao-wen HUANG (Journal of Integrative Agriculture, 2022)
Partial substitution of chemical fertilizers by organic amendments is adopted widely for promoting the availability of soil phosphorus (P) in agricultural production. However, few studies have comprehensively evaluated the effects of long-term organic substitution on soil P availability and microbial activity in greenhouse vegetable fields. A 10-year (2009–2019) field experiment was carried out to investigate the impacts of organic fertilizer substitution on soil P pools, phosphatase activities and the microbial community, and identify factors that regulate these soil P transformation characteristics. Four treatments included 100% chemical N fertilizer (4CN), 50% substitution of chemical N by manure (2CN+2MN), straw (2CN+2SN), and combined manure with straw (2CN+1MN+1SN). Compared with the 4CN treatment, organic substitution treatments increased celery and tomato yields by 6.9−13.8% and 8.6−18.1%, respectively, with the highest yields being in the 2CN+1MN+1SN treatment. After 10 years of fertilization, organic substitution treatments reduced total P and inorganic P accumulation, increased the concentrations of available P, organic P, and microbial biomass P, and promoted phosphatase activities (alkaline and acid phosphomonoesterase, phosphodiesterase, and phytase) and microbial growth in comparison with the 4CN treatment. Further, organic substitution treatments significantly increased soil C/P, and the partial least squares path model (PLS-PM) revealed that the soil C/P ratio directly and significantly affected phosphatase activities and the microbial biomass and positively influenced soil P pools and vegetable yield. Partial least squares (PLS) regression demonstrated that arbuscular mycorrhizal fungi positively affected phosphatase activities. Our results suggest that organic fertilizer substitution can promote soil P transformation and availability. Combining manure with straw was more effective than applying these materials separately for developing sustainable P management practices.